Development of Local Wisdom-Based "Sandal Wayang" Game Tools to Improve Physical Motor Ability of Children with Special Needs in Early Childhood Education Inclusion - Rachma Hasibuan; Ajeng Putri Pratiwi; Muhammad Reza; Melia Dwi Widayanti; Miftakhul Jannah (International Journal of Current Educational Research, 2022)
Childhood is an important period for development and an opportunity to learn and develop motor skills and physical fitness through Movement-based play. This research will develop a play tool, "sandal wayang" (sayang), based on wayang characters, namely the "punakawan" family, to improve the physical motor skills of children with special needs in Inclusive ECE. The development method used in this study is the ADDIE (Analyze, Development, Design, Implementation, Evaluation) model, with data collection through observation, surveys, and interviews. The targets of this development research trial were teachers and students at the Kharisma Sidoarjo Kindergarten institution. The product of this research is a "sayang" game with wayang characters from the Pandawa family (Semar, Petrok, Gareng, Bagong) and Gatotkaca, as well as a guidebook on how to use the "sayang" game. The results of the material and media validation state that the "sayang" game tool that has been developed is suitable for use in learning. The implementation results show that there is an increase in balance and coordination of movements before and after playing "sayang".